2014
DOI: 10.1007/s10544-014-9881-1
|View full text |Cite
|
Sign up to set email alerts
|

A nanostructured aluminum oxide-based microfluidic device for enhancing immunoassay’s fluorescence and detection sensitivity

Abstract: A nanostructured aluminum oxide (NAO)-based fluorescence biosensing platform with a programmable sample delivery microfluidic interface is reported. The NAO-based fluorescence sensor can tremendously enhance the fluorescence signals, typically up to 100 × or more, over the glass substrate. The programmable sample delivery microfluidic interface, which is integrated with the NAO-based sensors, can automatically generate and deliver a series of different concentrations of the biological samples to each individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The fabrication process of the anodic aluminum oxide (AAO) nanopore thin film sensor has been described in detail (He at al., 2014; Li et al, 2014; Li et al, 2013; He et al, 2012). This chip, consisting of arrayed nanopore-based sensors, has been fabricated using a newly developed process (Yin et al, 2014, Che et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The fabrication process of the anodic aluminum oxide (AAO) nanopore thin film sensor has been described in detail (He at al., 2014; Li et al, 2014; Li et al, 2013; He et al, 2012). This chip, consisting of arrayed nanopore-based sensors, has been fabricated using a newly developed process (Yin et al, 2014, Che et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The solution concentration gradient generator (Fig. 3C) was adapted from the tree-shaped microfluidic chip [38]. The size of the channels was 80 µm (height)  100 µm (width) with three inlets 1, 2, 3.…”
Section: B Microfluidic Chip Design and Fabricationmentioning
confidence: 99%
“…The photoluminescent intensity can be enhanced with metal nanostructures [ 39 ] and photonic crystals [ 40 ] fabricated on the sensor. Li et al [ 41 ] reported a nanostructured aluminium-oxide (NAO)-based photoluminescence platform that enhanced a photoluminescent signal up to 100 fold and promoted the photoluminescent-based immunosensing with high throughput. Protein A and fluorophore-labeled immunoglobulin G (IgG) were used to demonstrate that the IgG of programmable concentrations was confirmed with the photoluminescent images on the microfluidic device.…”
Section: Immunosensing With Optical Probesmentioning
confidence: 99%